3D topography and tomography of multilayered freeform optical surfaces using large-range measurement swept-source low-coherence interferometry. (29th August 2018) - Butola, Ankit; Joshi, Tilak; Ahmad, Azeem; Dubey, Vishesh; Senthilkumaran, P; Singh Mehta, Dalip
Abstract: Multilayered freeform optical surfaces are frequently used in various types of light-emitting diodes (LEDs) as encapsulant, light extraction, beam shaping and diffusing elements. We demonstrate optical metrology and sectioning of these types of optical surfaces by using a swept-source low-coherence interferometric (SS-LCI) system. This work reports the extended range of measurement of multilayered surfaces with high resolution. To validate the detection and measurement capability of SS-LCI, experiments are conducted on different LEDs having multilayered surfaces, e.g. step-sized, conical- shaped, dome-shaped red, green, blue and aspheric surfaces. 3D topographic and tomographic images of the aforementioned objects are obtained through various 2D X - Z scans of the sample beam with 12 μ m axial resolution. The instantaneous spectral linewidth of the swept source leads to large range of depth/height measurement (penetration depth ~12 mm) without any ambiguity problem. In addition, the acquisition speed of the system for scanning a large sample area (16  ×  16  ×  12 mm) is very high due to the fast wavelength sweeping speed of the micro-electromechanical system- vertical-cavity surface-emitting laser swept source. The measured 3D topography and tomography of freeform optical surfaces is further used to formulate their approximate profile and measure the distance between multilayered surfaces. Furthermore, the reconstructed 2D images corresponding to various freeform surfaces are converted into binary images by setting a certain threshold value and then is higher-order polynomial fitted to obtain profiles of the objects.